Tito Varisco - Autorimessa a Milano - Lisini, Caterina (Firenze Architettura, 2017)
With the garage in via De Amicis in Milan, Tito Varisco expresses a formal research in which function, structure and expression find an unusual synthesis. The refined grammar of fullness and voids, the expressive play of light and shadow, the dialectics between the shapes and the backdrop of the Milanese factory reveal a special affinity with Luigi Moretti's 'concrete' figurative research and plastic experimentation.